Prevalence of Obesity and Overweight among Staff at Technical Institute-Swaira in Middle Technical University - Kadhim Jawad, Ahmed; Abbas Okab , Ammar (Diyala Journal of Medicine, 2023)
Background: Overweight and obesity defined as "abnormal or excessive fat accumulation that presents a risk to health". Obesity is the fifth among global causes of death. The rise in overweight and obesity among adult workers is a global public health concern. It's associated with a higher risk of type 2 diabetes, hypertension, coronary heart disease, stroke, and cancer, as well as increased healthcare expenditures, reduced job productivity, and lost of money. Objective: To assess the prevalence of overweight and obesity and to find out relation with some risk factors among staff at Technical Institute-Swaira in Middle Technical University. Patients and Methods: A descriptive cross-sectional study design carried out in Technical Institute-Swaira in Middle Technical University. Included (150) of staff selected. Sampling Technique to selection staff were random (probability sampling). The data collection by direct interview technique of researcher with each participant of staff from 5th November 2021 to 4th July 2022. Results: The study show socio-demographic characteristics. Regarding to staff age (31-40) years constituted the majority (38.0%). High percentage of participants were married (84.7%) and lower percentage were divorced (1.3%), BMI in the study population the high percentage were (42.0%) of participants overweight, BMI was highly significantly by practicing exercise (P= 0.000), significant differences in BMI with regular three meals a day and eat fast food (P= 0.01), (P= 0.03). Conclusion: This study found that a large number of participant were overweight or obese. BMI changes a lot with age. There were big differences in BMI between participant who worked out regularly and participant who ate three meals a day or fast food.